Internal fixation of anterior acetabular fractures with a limited pararectus approach and the anatomical plates: preliminary results - Yao, Sheng (BMC Musculoskelet Disord, 2021)
BACKGROUND: The surgical treatment of acetabular fracture has adverse outcomes and high risk, and minimally invasive method is a good way to reduce complications and improve hip joint function. This study is to investigate the treatment of certain acetabular fractures primarily involving the anterior column and quadrilateral plate using a limited pararectus approach and the anatomical plates. METHODS: A consecutive cohort of 17 patients with anterior displaced acetabular fractures were managed operatively with a limited approach and the anatomical plates. Ten patients had anterior column fractures, 1 patient had anterior wall fracture, 4 patients had transverse fractures and 2 patients had anterior column with posterior hemi-transverse fractures. The inferior half of the pararectus approach was adopted to open the medial window and to access the anterior column and the quadrilateral plate. The anatomical plates were used for internal fixation. Residual displacements were assessed on the postoperative CT scans using a standardized digital method. The surgical details, hip functional outcomes, and complications were noted. RESULTS: All of the patients were operated using the limited pararectus approach and the anatomical plates successfully. The mean operative time and blood loss were 90.9 min and 334.1 ml, respectively. The average postoperative residual gap and step displacement on CT were 2.9 mm and 0.7 mm, respectively. The radiological outcome was estimated according to the Matta score, ten of the cases were graded anatomical, six were graded imperfect, and one was graded poor. Follow up averaged 15 months. Functional outcomes were excellent for nine, good for six, and fair for two. It was noted that one case of peritoneal injury was repaired intraoperatively. CONCLUSIONS: The limited pararectus approach with the advantages of less trauma, direct exposure to the anterior column and quadrilateral plate. The anatomical plates can fit with the surface of the acetabulum, which saves the time of remodeling plates during operation and facilitate fracture reduction. The combination approach can be a good choice for limited surgery of displaced anterior acetabular fractures especially involving the quadrilateral plate. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12891-021-04034-w.